Variasi Media Pendingin Proses Pengecoran Terhadap Kekuatan Material Dan Struktur Mikro Pada Pengecoran Aluminium ADC12 - Ningsih, Pita Dwi Rahayu; Umar, Mega Lazuardi; W.W, Prabuditya Bhisma; Hanafi, Agung Fauzi; P.U, Rochmad Eko (Rekayasa Material, Manufaktur dan Energi, 2024)
Metal casting can influence the mechanical properties and materials’s microstructure such as aluminum. The mechanical properties, strength, and microstructural form are affected by the solidification process during casting. These changes occur due to the cooling media used in the solidification process. The mechanical properties of metals, especially material strength, are crucial in today's manufacturing industry. This research investigates various cooling media in the casting process, including air, radiator coolant, and oil. Tensile tests and microstructural analysis were conducted to determine the mechanical properties and grain structure of the castings. The tensile testing showed that the highest tensile strength was achieved with radiator coolant at 146.305 MPa, followed by oil at 141.297 MPa, and the lowest with air at 131.431 MPa. Microstructural analysis revealed that the finest grains were obtained with oil cooling, while the largest grains were observed with air cooling.